University extension project and the development of the critical - thinking on mining engineering and geology students (Research, Society and Development, 2019)
All scientific knowledge must be constructed based on its impact on society; and one of the ways to work this critical- thinking on engineering students is through extension practice. The present paper evaluated - through a questionnaire - 20 students who participated in the Education, Geoscience and Mining extension program of UFMT whose participants are graduates in mining engineering or geology. In this evaluation the questions asked involved themes such as the student's interest in the course and university before and after the project, if they participated in any scientific event during the extension, if they are more prepared to discuss questions about their profession after the project, among others. As a result, those who were part of the program are more inserted, adapted and prepared to speak in public about the themes they worked on than before. It is concluded that the critical formation of the engineering student is enhanced when it is associated with a contextualized practice. The university extension project allowed mine engineering and geology students to reflect on the impact of their future profession.